(f-g)(x) = x²+6x - (7-x)
(f-g)(x) = x² + 6x - 7 + x
(f-g)(x) = x² + 7x - 7
(f-g)(9) = 9² + 7*9 - 7
(f-g)(9) = 81 + 63 - 7
(f-g)(9) = 137
Answer:
Find the common like terns in each expression!
Step-by-step explanation:
For example A:
+3y +2x -2y +5z
+3y -2y = 1y or y
Then sort by the greatest values:
5z+2x+1y
The question is asking us to find how much seven tomatoes would cost. Well, to get our answer, we must first find the cost of one tomato. We are given the information that paying $4.16 for 4 tomatoes. All we have to do now is divide 4.16 by 4, to get the price of one tomato. This gives us $1.04. Now, just multiply 1.04 by 7 to get 7.28. Therefore, the price of seven tomatoes is C. $7.28. Hope this helped and have a phenomenal day!